2020
DOI: 10.2209/tdcpublication.2019-0036
|View full text |Cite
|
Sign up to set email alerts
|

Interdental Distraction Osteogenesis in Unilateral Cleft Lip and Palate Patient with Wide Alveolar Cleft

Abstract: Alveolar bone grafting is routinely performed in repair of alveolar clefts. When the alveolar cleft is wider than 11 mm, however, the survival rate of the bone graft and prognosis are poor. Here, we describe successful orthodontic treatment using interdental distraction osteogenesis (IDO) with a tooth-tooth type distractor to reduce the width of the alveolar cleft in a patient with unilateral cleft lip and palate. The patient was a 12-yearold girl with unilateral cleft lip and palate, maxillary dentition midli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Bone-borne devices were used in this study because previous research found that tooth-borne devices result in more dental movements than bony movements. A bone-borne distractor placed above the transport segment may also help to reduce superior tilting 4,5 . There was no relapse in this study's follow-up period (which lasted 6–18 months).…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Bone-borne devices were used in this study because previous research found that tooth-borne devices result in more dental movements than bony movements. A bone-borne distractor placed above the transport segment may also help to reduce superior tilting 4,5 . There was no relapse in this study's follow-up period (which lasted 6–18 months).…”
Section: Discussionmentioning
confidence: 74%
“…During mixed dentition, alveolar cleft closure in conjunction with orthodontic treatment has become a widely accepted treatment choice 1,2 . Secondary grafting provides adequate bone support for teeth adjacent to the cleft area, a bony environment for teeth eruption in the cleft site, a bony continuity in the maxillary alveolar ridge, and a satisfactory alveolar bone contour, arch width support to prevent maxillary arch collapse, elimination of oronasal fistulas, improved facial symmetry, and improved oral hygiene status 3–6 …”
mentioning
confidence: 99%